The Design and Development of Hybrid Pico Hydro-Solar Fountain for Power Generation - Robert, Davidson; Norjali, Rasida; Mashori, Sumaiya (Progress in Engineering Application and Technology, 2023)
In this era of globalization, electricity that are being generated by the big company that feed us the electricity power to cities and villages has made our civilization are highly dependent on electricity.  With the supply of electricity to the cities and many industrial facilities, the productivity of the economy rise high and the demand of electricity is very high in every places in the world. Due to the high demand of the electricity energy, the bill of the electricity is also high. In case for the low household income family especially the one that living in a poor area and the electricity supplies may not reach it, they will need another method of acquiring electricity for their daily life usage. Such as diesel fueled generator. However the diesel fueled generator is not a free energy that can produce electricity endlessly because it requires diesel fuel to start generating electricity. There is other method of generating free electricity power, that is by using hydroelectric and solar power. Therefore, this project aim is to create a pico-sized hybrid hydro-solar generator that is small enough to be placed inside home. The project is to create a eco-friendly electrical power generator without consuming any other material but only with endless running water and the sunlight energy using DC motor and solar panel. The prototype of this project aim is to generate 5V energy that can charge up 5V battery and be used as a power supply to many other appliances like the Arduino, ESP8266, water pump, LED lights and able to charge up smartphones and many other things that requires 5V voltage to be able to charge